Reproductive production constraints within the New Zealand racing industry - Rogers CWW; Gee EK; Bolwell CF (Massey University, 2016)
The New Zealand Thoroughbred industry has seen rationalisation in response to changes in the domestic market and more recently the Global Financial Crisis (GFC). To quantify changes in production, end-of-season reproductive data for active Thoroughbred sires were extracted for the 1989/90 to 2011/12 breeding seasons. There were reductions in the numbers of mares bred and foals produced (10,176 mares & 5,882 foals vs. 5,826 mares & 3,927 foals, respectively in 1989/90 and 2011/12 seasons) resulting in a greater relative proportion of foals registrations (57% vs. 67%). During this period, the number of active sires decreased (265 vs. 94) and number of mares per sire increased (33 IQR 18-53 vs. 49 29-91). The 2007/08 season (GFC) was associated with an acute reduction in the number of shuttle stallions imported for breeding (from 23% in 2006/07 to 11% of active sires in 2007/08), and a temporary increase in number of mares bred (13%), in response to the 2007 Equine Influenza outbreak in Australia. The proportion of sires covering >100 mares per season increased from 6% (1989/90) to 25% (2011/12). Despite the reduction in active broodmares during the same period (43%), there has not been a proportional decrease in export numbers (24%) or domestic numbers of horses racing (6.5%).
Keywords: horse; equine; Thoroughbred; racing; reproduction; 0702 Animal Production